The Impact of Caste: A Missing Link in the Literature on Stunting in India - Rajesh Ramachandran; Ashwini Deshpande (Institute of Labor Economics (IZA), 2021)
India is home to some 120 million children under the age of 5, 36 percent of whom are chronically malnourished. The associated high prevalence of stunting has generated a stream of research explaining why chronic malnourishment in India is higher than in poorer countries of sub-Saharan Africa. Surprisingly, this body of research has overlooked a crucial feature of chronic malnourishment in India – that is, the difference in stunting incidence across caste and religious groups. A comparison by social categories reveals that not only are the height gaps between social groups in India two to three times larger than the India–Africa gap, but that children from the socio-economically dominant group, the upper caste Hindus, are even taller than their African counterparts. We find significant caste gaps in child height in samples that are balanced on an extensive set of covariates. We also show that height gaps are higher in areas where discrimination is more prevalent. Our results suggest that incorporating considerations of caste is essential to understanding the problem of chronic malnourishment in India today.
Keywords: I1; J13; J24; 330; early childhood development; stunting; malnourishment; caste; India